2003
DOI: 10.1042/bst0310202
|View full text |Cite
|
Sign up to set email alerts
|

Malonyl-CoA and AMP-activated protein kinase (AMPK): possible links between insulin resistance in muscle and early endothelial cell damage in diabetes

Abstract: Based on available evidence, we would propose the following. (i) Excesses of glucose and free fatty acids cause insulin resistance in skeletal muscle and damage to the endothelial cell by a similar mechanism. (ii) Key pathogenetic events in this mechanism very likely include increased fatty acid esterification, protein kinase C activation, an increase in oxidative stress (demonstrated to date in endothelium) and alterations in the inhibitor κB kinase/nuclear factor κB system. (iii) Activation of AMP-activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(76 citation statements)
references
References 48 publications
0
74
0
2
Order By: Relevance
“…Second, pancreatic beta cell damage in the ZDF rat has been related to ceramide-induced apoptosis [39], and AICAR, by activating AMPK, has been shown to inhibit apoptosis in human umbilical vein endothelial cells [43] and astrocytes [44] incubated with palmitate or a high concentration of glucose. Furthermore, in some of these studies AICAR was shown to inhibit de novo ceramide synthesis and decrease the activity of serine palmitoyl transferase, the first committed enzyme in the de novo ceramide synthesis pathway [44,45]. Third, in endothelial cells incubated with an elevated concentration of glucose or NEFA, AICAR, and, where studied, expression of a constitutively active AMPK, inhibited oxidative stress, mitochondrial damage and the activation of NFκβ and caspase-3 [44,45].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Second, pancreatic beta cell damage in the ZDF rat has been related to ceramide-induced apoptosis [39], and AICAR, by activating AMPK, has been shown to inhibit apoptosis in human umbilical vein endothelial cells [43] and astrocytes [44] incubated with palmitate or a high concentration of glucose. Furthermore, in some of these studies AICAR was shown to inhibit de novo ceramide synthesis and decrease the activity of serine palmitoyl transferase, the first committed enzyme in the de novo ceramide synthesis pathway [44,45]. Third, in endothelial cells incubated with an elevated concentration of glucose or NEFA, AICAR, and, where studied, expression of a constitutively active AMPK, inhibited oxidative stress, mitochondrial damage and the activation of NFκβ and caspase-3 [44,45].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, in some of these studies AICAR was shown to inhibit de novo ceramide synthesis and decrease the activity of serine palmitoyl transferase, the first committed enzyme in the de novo ceramide synthesis pathway [44,45]. Third, in endothelial cells incubated with an elevated concentration of glucose or NEFA, AICAR, and, where studied, expression of a constitutively active AMPK, inhibited oxidative stress, mitochondrial damage and the activation of NFκβ and caspase-3 [44,45]. All of these effects could have contributed to the observed actions of AICAR administration on the islets.…”
Section: Discussionmentioning
confidence: 99%
“…The high molecular weight and hexameric isoforms of ACRP30 also activate NF-B (3). On the other hand, recent studies by Ido and his coworkers (41,42) have shown that AMPK activation by AICAR or expression of a constitutively active AMPK can inhibit NF-B-mediated gene expression in both cultured human umbilical vein endothelial cells and COS7 cells. Thus, the interaction of gACRP30 and the various oligomeric forms of ACRP30 in regulating NF-B activity, and in turn its relevance to their biological actions, clearly requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…AMPK plays an important role in regulating the energy balance in the myocardium; the activation of AMPK during ischemia-reperfusion can reduce ischemia-induced necrosis and apoptosis (23,39). The increase in the cellular AMP-to-ATP ratio is a major regulator of AMPK activity (23,38), but adiponectin has also been reported to activate AMPK (21,38). Most of the beneficial effects of adiponectin are reportedly mediated by AMPK-associated signaling (21).…”
Section: Effect Of Cr On Myocardial Ischemia-reperfusion Injury and Ipcmentioning
confidence: 99%